Vertebrate community composition and diversity declines along a defaunation gradient radiating from rural villages in Gabon. Issue 3 (1st November 2016) - Koerner, Sally E.; Poulsen, John R.; Blanchard, Emily J.; Okouyi, Joseph; Clark, Connie J.
Summary: Anthropocene defaunation is the global phenomenon of human‐induced animal biodiversity loss. Understanding the patterns and process of defaunation is critical to predict outcomes for wildlife populations and cascading consequences for ecosystem function and human welfare. We investigated a defaunation gradient in north‐eastern Gabon by establishing 24 transects at varying distances (2–30 km) to rural villages and surveying the abundance and composition of vertebrate communities. Distance from village was positively correlated with observations of hunting (shotgun shells, campfires, hunters), making it a good proxy for hunting pressure. Species diversity declined significantly with proximity to village, with mammal richness increasing by roughly 1·5 species every 10 km travelled away from a village. Compared to forest far from villages, the wildlife community near villages consisted of higher abundances of large birds and rodents and lower abundances of large mammals like monkeys and ungulates. Distance to nearest village emerged as a key driver of the relative abundance of five of the six taxonomic guilds, indicating that the top‐down force of hunting strongly influences large vertebrate community composition and structure. Several measures of vegetation structure also explained animal abundance, but these varied across taxonomic guilds. Forest elephants were the exception: no measured variable or combination of variables explained variation in elephant abundances. Synthesis and applications . Hunting is concentrated within 10 km around villages, creating a hunting halo characterized by heavily altered animal communities composed of relatively small‐bodied species. Although the strongest anthropogenic effects are relatively distance‐limited, the linear increase in species richness shown here even at distances 30 km from villages suggests that hunting may have altered vertebrate abundances across the entire landscape. Central African forests store >25% of the carbon in tropical forests and are home to 3000 endemic species, but roughly 53% of the region lies within the village hunting halo. Resource management strategies should take into account this hunting‐induced spatial variation in animal communities. Near villages, resource management should focus on sustainable community‐led hunting programmes that provide long‐term supplies of wild meat to rural people. Resource management far from villages should focus on law enforcement and promoting industry practices that maintain remote tracts of land to preserve ecosystem services like carbon storage and biodiversity. Abstract : Hunting is concentrated within 10 km around villages, creating a hunting halo characterized by heavily altered animal communities composed of relatively small‐bodied species. Although the strongest anthropogenic effects are relatively distance‐limited, the linear increase in species richness shown here even at distances 30 km from villages suggests that hunting may have altered vertebrate abundances across the entire landscape. Central African forests store >25% of the carbon in tropical forests and are home to 3000 endemic species, but roughly 53% of the region lies within the village hunting halo. Resource management strategies should take into account this hunting‐induced spatial variation in animal communities. Near villages, resource management should focus on sustainable community‐led hunting programmes that provide long‐term supplies of wild meat to rural people. Resource management far from villages should focus on law enforcement and promoting industry practices that maintain remote tracts of land to preserve ecosystem services like carbon storage and biodiversity.